A Moderated Mediation Model of Lean, Agile, Resilient, and Green Paradigms in the Supply Chain - Shaker Ahmed Alqudah; Hosam Shrouf; Taghrid Suifan; Salah Alhyari (International Journal of Supply Chain Management, 2020)
Abstract— Theorizing and moderated mediation analysis enables supply chain management scholars and practitioners to extend the boundaries of our present knowledge by examining how, when, and why lean, agile, resilient, and green association to capabilities, sustainability, and performance occur. However, only a limited number of studies have addressed this issue because of the complexities associated with their execution. In this article, we provide primary data on capabilities, sustainability, and performance in the supply chain contexts of a detailed model. Also, a widespread review of the literature was presented to motivate the underlying measures associated with the supply chain management paradigms, supply chain capability, sustainability, and performance used to create the study model. This review and subsequent model are intended to support future theoretical and practical investigations of supply chain management paradigms across complex and comprehensive relationships.